Analisis Strategi Mutu Produk Indomie Untuk Memenuhi Standarisasi Pasar Global - Suhairi, Suhairi; Hayatunnufus, Annisah Fildzania; Utami, Annisa Dwi; Lubis, Listiya Andana; Putri, Tasya Yustika (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The purpose of this research is to find out how Indomie's product quality strategy can be analyzed to meet global market standards. Qualitative research is used as a research method, namely: 1) descriptive and explorative; 2) describe and explain. Based on the discussion, it can be concluded that an analysis of Indomie's product quality strategy to meet global market standards can be carried out through 1) Production strategy, carrying out continuous innovation, building factories overseas, product standardization and quality maintenance. 2) Location determination strategy, taking into account distribution channels, sales areas, storage locations, inventory levels and locations and transportation systems. 3) Promotional strategy, Indomie has a slogan that is very simple but suitable and easy for people to remember, namely, "Indomie is my taste" while the name or brand of Indomie is one of the successful products, so its products are widely known, especially among Indonesian people. 4) Strategies for building relationships with consumers, namely noodle communities, distribution channels, partners, health facilities, supply chains, electronic print media and pricing strategies.